THE ROLE OF LAUGHTER IN UZBEK LITERATURE - Tashmukhamedova, Latofat (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
The article analyzes the importance of humor and satire in social life, the aesthetic function of satire, and the role of satire in the moral development of individuals, using the humorous works of Abdulla Qodiriy as an example. Qodiriy's contemporaries and the modern literary critics' theoretical observations on satire and humor, the deep roots of Uzbek humor, and its stages of development are explained. The events and incidents depicted in humor are taken from real life, revealing their social significance, the role they play in humor, their impact, and their task of exposing shortcomings in society. The early works created based on satire and humor in Uzbek literature can be attributed to A. Qodiriy's creativity, so the works "Scorpion from the Altar", "From the memoirs of Kalvak Makhzum", "What does Toshpulat Tajang say?" were selected as the objects of the article. In his comedic works, the writer does not follow the path of one-sided condemnation and exposure of certain negative phenomena in life and human nature from a purely ideological point of view. In the chapter "Buffoons" in the novel «Scorpion from the Altar", the public and festive humor is akin to the carnival scene in European literature, and the discussion is based on excerpts from the work, where the shortcomings in society are directly addressed to the authorities through the humors of the very characters. The article explains that initially the content of the magazine "Mushtum" was intended only for humorous articles, however, a discussion took place on this issue with Gozi Yunusov, and "Mushtum" in subsequent years became a platform for expressing political and ideological opinions contrary to the nature of the magazine. Based on the facts, it is proved that Abdullah Kadiri did not support the lack of skill and humor in the magazine. The hermeneutic analysis method was used in the research process.
Keywords: laughter; comedy; image; humor; satire; influence; emotion; exaggeration